A Statistical Analysis study on Company B - LaMadrid, Maria Inez; Poblete, Natalie Ian.; Villanueva, Racquel (Diliman, Quezon City College of Engineering, 2002)
Co. B is a multinational company, which manufactures battery types. A statistical study was conducted in Co. B to identify which factors are significant on the number of its rejections. The group focused on the curing process since it yielded the highest number of nonconformities. Curing is the process of preparing the plates, which are the raw materials in the manufacture of batteries, for charging. After analyzing the problems in the curing process, three main problems were determined to contribute to the reprocessing of plates : (1) excess in percent Free Metallic Lead (FML), (2) excess in percent moisture content after curing, and (3) vibration loss. Using the Pareto Chart, the researchers found out that excess in percentFML contributed to the highest number of nonconformities in the plates. Another tool used by the group is an Ishikawa Diagram, which presented the factors affecting the variations of percentFML. The following factors are: (1) temperature in the curing booth, (2) relative humidity, (3) initial moisture content and (4) air coming into the vent. For the purpose of this study however, the group only considered the first three factors since the last factor cannot be quantified. A 2 3 Factorial Design was chosen as the most appropriate experimental design for the study. The factors selected for the experiment were temperature (a), relative humidity (b) and initial moisture content (c) Two levels were considered for each factor : T1 and T2 for temperature, RH1 and RH2 for relative humidity and M1 and M2 for initial moisture content. The response variable chosen is the measured deviations of percent FML with its standard limit. Statistical analyses were done to determine which factors are significant on the response variable. A Goodness-of-Fit Test was applied which proved that the data the group gathered follow a normal distribution. This was helpful in proving the validity of our sample size. The Analysis of Variance (ANOVA) for Fixed Effects Model identified factor a, b, c and interaction ac to have significant effects on percentFML. Finally, a Residual Analysis was done which determined the best combination of factors for the experiment. Factor b has the least variability of error which means that a and c should have low levels and b should have a high level. Based on the results, the group recommends that the company should take corresponding measures to control these factors at these levels. Combination b contributes the greatest conversion of Free Metallic Lead into Lead Oxide in the plates, which means that it minimizes the number of reprocessed plates during the curing process.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics